Peptidoglycan Association of Murein Lipoprotein Is Required for KpsD-Dependent Group 2 Capsular Polysaccharide Expression and Serum Resistance in a Uropathogenic Escherichia coli Isolate - Jingyu Diao (American Society for Microbiology, 2017)
ABSTRACT Murein lipoprotein (Lpp) and peptidoglycan-associated lipoprotein (Pal) are major outer membrane lipoproteins in Escherichia coli. Their roles in cell-envelope integrity have been documented in E. coli laboratory strains, and while Lpp has been linked to serum resistance in vitro, the underlying mechanism has not been established. Here, lpp and pal mutants of uropathogenic E. coli strain CFT073 showed reduced survival in a mouse bacteremia model, but only the lpp mutant was sensitive to serum killing in vitro. The peptidoglycan-bound Lpp form was specifically required for preventing complement-mediated bacterial lysis in vitro and complement-mediated clearance in vivo. Compared to the wild-type strain, the lpp mutant had impaired K2 capsular polysaccharide production and was unable to respond to exposure to serum by elevating capsular polysaccharide amounts. These properties correlated with altered cellular distribution of KpsD, the predicted outer membrane translocon for “group 2” capsular polysaccharides. We identified a novel Lpp-dependent association between functional KpsD and peptidoglycan, highlighting important interplay between cell envelope components required for resistance to complement-mediated lysis in uropathogenic E. coli isolates. IMPORTANCE Uropathogenic E. coli (UPEC) isolates represent a significant cause of nosocomial urinary tract and bloodstream infections. Many UPEC isolates are resistant to serum killing. Here, we show that a major cell-envelope lipoprotein (murein lipoprotein) is required for serum resistance in vitro and for complement-mediated bacterial clearance in vivo. This is mediated, in part, through a novel mechanism by which murein lipoprotein affects the proper assembly of a key component of the machinery involved in production of “group 2” capsules. The absence of murein lipoprotein results in impaired production of the capsule layer, a known participant in complement resistance. These results demonstrate an important role for murein lipoprotein in complex interactions between different outer membrane biogenesis pathways and further highlight the importance of lipoprotein assembly and transport in bacterial pathogenesis.